Ten-Year and Beyond Follow-up After Treatment With Highly Purified Liquid-Injectable Silicone for HIV-Associated Facial Lipoatrophy: A Report of 164 Patients. Issue 7 (July 2019) - Jones, Derek H.; Carruthers, Alastair; Brody, Harold J.; Black, Jeanette M.; Humphrey, Shannon; Carruthers, Jean; Wesley, Naissan O.; Minokadeh, Ardalan
Abstract : BACKGROUND: Highly purified liquid-injectable silicone (LIS) has been established as a permanent agent for off-label correction of HIV-associated facial lipoatrophy (HIV-FLA). However, controversy exists about long-term safety. OBJECTIVE: To establish the safety and efficacy at 10 years or greater of LIS for HIV-FLA. METHODS: Patients from 3 practices with 10-year or greater in-person office follow-up were analyzed to determine the number of LIS treatments and total volume required to achieve optimal correction. The nature of any treated adverse events was noted. RESULTS: One hundred sixty-four patients had 10-year or greater in-office follow-up. All subjects maintained long-term correction with an average of 9 treatments, average of 1.56 mL per treatment, and an average total of 14.1 mL. Two patients had severe adverse events manifesting as temporary facial edema. Four patients experienced mild-to-moderate excess fibroplasia presenting as perceived overcorrection, and 6 patients had nondisfiguring subcutaneous firmness. All adverse events were successfully treatable, mostly with intralesional 5-fluorouracil and triamcinolone. CONCLUSION: Liquid-injectable silicone is an effective long-term treatment option for HIV-FLA. When injected in small quantities with the microdroplet serial puncture technique at monthly or greater intervals, optimal correction appears durable for more than 10 years. Adverse events consisted mostly of excess fibroplasia and were treatable.